Pharmaceutical industry of Bangladesh and the exposure of BRAC Bank Limited on the sector - Bristy, Sanjida Nahar (BRAC University, 2013)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2012.